THE INFLUENCE OF EDUCATION LEVEL, BUSINESS AGE, AND ACCOUNTING TRAINING ON FINANCIAL REPORTING OF MSMEs BASED ON STANDAR AKUNTANSI KEUANGAN ENTITAS MIKRO, KECIL, DAN MENENGAH (SAK EMKM) - Habibah, Zahratunisa; Astuti, Tutut Dewi (Universitas Nusa Cendana, 2024)
This study examines how the effect of education level, length of business, and accounting training on the preparation of MSME financial statements based on Standar Akuntansi Keuangan Entitas Mikro, Kecil, dan Menengah (SAK EMKM) or Financial Accounting Standards for Micro, Small, and Medium Enterprises (FAS MSMEs) in Kalibawang District. MSMEs play a significant role in the Indonesian economy, yet managing their finances presents numerous difficulties. A Likert questionnaire was used to gather the data, and multiple linear regression was used for analysis. The findings indicate that the only factor that significantly affects the preparation of MSMEs' financial statements is accounting training; neither the age of the company nor the degree of education have any bearing. This study highlights the accounting training is essential for enhancing the financial understanding of MSMEs players in the application of SAK EMKM. Keywords: Education Level; Length Of Business; Accounting Training; Financial Statements; Standar Akuntansi Keuangan Entitas Mikro, Kecil, dan Menengah (SAK EMKM); Financial Accounting Standards for Micro, Small, and Medium Enterprises (FAS MSMEs)